COMPARISON OF CYTHOCROME P450 FAMILY 2 SUBFAMILY A POLYPEPTYDE 6 (CYP2A6) GENE POLYMORPHISM PROPORTION ON EARLY AND ADVANCED STAGE OF UNDIFFERENTIATED TYPE NASOPHARYNGEAL CARCINOMA IN BALINESE - I Gde Ardika Nuaba; Komang Andi Dwi Saputra; I Ketut Suanda; I Gusti Ayu Trisna Dewi (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2019)
Introduction Nasopharyngeal carcinoma (NPC) is a malignancy derived from epithelial cells lining the nasopharynx. The etiology of nasopharyngeal carcinoma is multifactorial. One of the risk factors is CYP2A6 gene polymorphism which causes nitrosamines are not metabolized, leading to DNA change that could trigger cancer. Objectives The purpose of this study is to know the association of CYP2A6 gene polymorphism and clinical stage of undifferentiated type of NPC Material and Method This is a cross sectional analytic study. The sample in this study were 80 nasopharyngeal carcinoma patients whose treated in ENT-HN department of Sanglah General Hospital between 2017 - 2018. The collected data consist of subject’s characteristic and CYP2A6 gene polymorphisms identified by the PCR-RFLP technique. Results The probability of CYP2A6 gene polymorphism in the undifferentiated type of NPC in the Balinese tribe is 3.125 times greater in advanced stage than early stage. Based on multivariate analysis, there was a statistically significant association between CYP2A6 gene polymorphism and clinical stage of undifferentiated type NPC in Balinese with p value = 0,0048 (p < 0,05). Conclusion There is association between CYP2A6 gene polymorphism and clinical stage of undifferentiated type NPC in Balinese tribe.